The Role of Digital Workflow in Customizing the Prosthetic Solutions: A Literature Review - Mukesh Soni; Prince Soni; Prithvi Soni; Sakshi Chokhandre; Merlin Moni; Samruddhi Gupta (Journal of Pharmacy and Bioallied Sciences, 2025)
Digital dentistry has revolutionized prosthodontics, enhancing efficiency, precision, and patient satisfaction. This literature review analyses the impact of digital workflows on prosthodontic practice, highlighting increased accuracy, reduced material waste, and improved time management. Furthermore, it demonstrates enhanced patient comfort and superior treatment outcomes associated with digital techniques, while also acknowledging potential limitations. This comprehensive assessment underscores the transformative potential of digital technologies in delivering personalized prosthodontic care.